ANALISIS KOMODITAS UNGGULAN SEKTOR PERTANIAN DI KABUPATEN SAMBAS - ME, YULIANSYAH (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTThe title of this research is the analysis of agricultural commodities inSambas district. National Development Goals is to improve the lives and welfare of thecommunity. In order to improve the welfare of the community, local authoritiesshould seek to increase people's income. Increase in income can be done throughthe development of existing regional potential through superior sector owned. If these advantages can be developed is expected to add to incomes. Thelargest sector contributing to GDP Sambas district is the agricultural sector, inorder to develop the sector, it is necessary to know what commodities areconsideredsuperior. This study has the purpose of: (1). Identifying agricultural commodities inSambas district, (2). Analyzing the various agricultural commodities in Sambasdistrict. This study uses secondary data. Where the secondary data obtained fromSambas Book Yearbook, Yearbook Kalbar Central Bureau of Statistics for the fiveyears from 2006-2010 observations.Analysis tool used is the Location Quotient, Shift-share and KlassenTypologi. The results showed that agricultural commodities rice, soy beans, greenbeans, fruit, coconut, pepper, coffee, cattle, goats, broiler chickens, ducks and seafishing.Sub-sectors that have higher competitiveness compared to similar sub-sector in West Kalimantan province is Crop sub-sector, fisheries and subpeternakan.sedangkan priority sectors to be developed is the plantation sub-sector.Growth in commodity structure is more advanced and is fast growingsoybeans, green beans, fruit, chicken meat, free-range chicken, sea fisheries.Commodities are classified as fast growing maize, cassava, yams, palm oil, cocoa,rubber, laying hens, public waters. Commodities are quite advanced but is slowgrowing paddy, coconut, pepper, goat. Commodities which are relativelydisadvantaged are vegetables, coconut Hybrida, pigs, buffalo, aquaculture.Keywords: Agriculture, Commodities, and agricultural commodity priorities